Molecular Typing and Resistance Profile of Acinetobacter baumannii Isolates during the COVID-19 Pandemic: Findings from the "EPIRADIOCLINF" Project - Antonella Agodi; Arturo Montineri; Rosa Manuele; Paola Noto; Giuseppe Carpinteri; Giacomo Castiglione; Patrizia Grassi; Antonio Lazzara; Anna Rita Mattaliano; Giuseppa Granvillano; Claudia La Mastra; Maria Clara La Rosa; et al. (MDPI AG, 2023)
Due to the COVID-19 pandemic, there has been a shift in focus towards controlling the spread of SARS-CoV-2, which has resulted in the neglect of traditional programs aimed at preventing healthcare-associated infections and combating antimicrobial resistance. The present work aims to characterize the colonization or infection with Acinetobacter baumannii of COVID-19 patients and to identify any clonality between different isolates. Specifically, data and resistance profiles of A. baumannii isolates were prospectively collected from patients recruited by the EPIRADIOCLINF project. Pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST) were used for molecular typing. Overall, we analyzed 64 isolates of A. baumannii from 48 COVID-19 patients. According to our analysis, we have identified the spread of a clonally related isolate, referred to as B. The PFGE pattern B includes four subtypes: B1 (consisting of 37 strains), B2 (11), B3 (5), and B4 (2). Furthermore, in the isolates that were examined using MLST, the most observed sequence type was ST/281. In terms of resistance profiles, 59 out of the total isolates (92.2%) were found to be resistant to gentamicin, carbapenems, ciprofloxacin, and tobramycin. The isolation and identification of A. baumannii from COVID-19 patients, along with the high levels of transmission observed within the hospital setting, highlight the urgent need for the implementation of effective prevention and containment strategies.